The effects of acute physical and cognitive exercises on sequential motor skill learning: An exploratory study - Guillaume Digonet; Thomas Lapole; Gabrielle Pouilloux; Ursula Debarnot (PLoS ONE, 2025)
Physical or cognitive exercises before motor skill learning are increasingly examined as a means to optimize performance during acquisition and consolidation processes. However, their respective effects remain underexplored in explicit sequential motor learning (SML). In this study, we examined whether different types of acute exercises such as sprint interval exercise, cognitive exercise, and a combination of both executed prior to explicit SML could modulate motor performance during acquisition and consolidation relative to a control group performing a neutral task. A total of 60 participants were randomly assigned to one of the four experimental groups. The psychophysiological modulations induced by the exercises were assessed using the NASA-TLX questionnaire and blood lactate measurements. Motor performance was evaluated at the beginning and the end of SML acquisition (early- and late-acquisition) and following delayed consolidation at 24h and one week later. Physical exercise elicited an increase in both lactate levels and subjective physical demand, while cognitive exercise increased mental demand. Overall, motor performance improved during both acquisition and consolidation at 24h and a week later, but without any difference between groups. Our findings suggest that neither sprint interval exercise, cognitive exercise, nor their combined execution prior to explicit SML significantly influences motor skill performance during acquisition and consolidation compared to a control intervention, although this absence of significant effects should be interpreted with caution.